A quarter century of management research in South Asia – II: India and Pakistan. (4th March 2019) - Menon, Sanjay T.
Abstract : Purpose: In part-I of this review series, research from Afghanistan, Bangladesh, Bhutan, Maldives, Nepal and Sri Lanka was reviewed. The purpose of this paper which is part-II of the series, is to review management research from India and Pakistan over a 25-year period from 1990 to 2014. Design/methodology/approach: A systematic review approach was adopted for this research. As a quality standard for inclusion, articles were restricted to journals rated A*, A, or B by the Australian Business Deans Council in 2013 and either Q1 or Q2 in the Scopus/Imago classification system. The divisions and interest groups of the Academy of Management were used as framework to organize the search results. Findings: A total of 1, 039 articles related to India ( n = 930) and Pakistan ( n = 112) emerged from the search process, with three articles being related to both countries. The research was published in 163 different journals that met the quality criteria. The period under review coincides with the advent of economic liberalization in India and this emerged as a major theme in the India-related research. Other context-specific insights for these two countries are also derived from an ecological and institutional theory perspective. Originality/value: This research represents the first comprehensive and systematic review of management research in India and Pakistan. As in part-I, the unique review approach allows for strict adherence to a predetermined quality standard while including a wide variety of journals and research traditions.